2021
DOI: 10.22146/ijc.69448
|View full text |Cite
|
Sign up to set email alerts
|

Computational Design of Thioxanthone Derivatives as Potential Antimalarial Agents through <i>Plasmodium falciparum</i> Protein Inhibition

Abstract: Plasmodium falciparum (P. falciparum) is the most fatal among the other Plasmodium parasites that infect humans with the malaria disease. Currently, the resistance of P. falciparum against some antifolate drugs has become a severe problem. On the other hand, xanthone and thioxanthone derivatives have been reported to have remarkable antimalarial activity. However, molecular docking studies have not evaluated thioxanthone derivative compounds as antimalarial agents. Accordingly, this research investigated the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Hydrophobic interactions with several amino acids, such as Leu46, Met55, and Phe58, strongly supported the stability of the complex between compound C90 and the quadrupole mutant PfDHFR. 27…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Hydrophobic interactions with several amino acids, such as Leu46, Met55, and Phe58, strongly supported the stability of the complex between compound C90 and the quadrupole mutant PfDHFR. 27…”
Section: Molecular Dockingmentioning
confidence: 99%
“…Along the same lines, another study evaluated, using molecular docking, binding poses, the mechanism of inhibition of various thioxanthone derivatives against P. falciparum DHODH and DHFR proteins. Few studies have examined the binding of Pf DHODH.…”
Section: Introductionmentioning
confidence: 99%
“…Alzain et al 24 identified potential new Pf DHODH inhibitors through computational screening using molecular docking, MM-GBSA calculations, ADME filtering, and molecular dynamics simulations. Along the same lines, another study evaluated, using molecular docking, binding poses, the mechanism of inhibition of various thioxanthone derivatives against P. falciparum DHODH and DHFR 25 proteins. Few studies have examined the binding of Pf DHODH.…”
Section: ■ Introductionmentioning
confidence: 99%